Guillain-Barré syndrome associated with viral infections (Research, Society and Development, 2020)
Guillain-Barré Syndrome has several negative consequences depending on the severity of its symptoms. The loss of functional independence is one of the factors that most interfere in the quality of life, making it harmful; in addition, it should be noted that it is a multifactorial disease. Thus, this research aimed to analyze the relationship between Guillain-Barré Syndrome and viral infections. This is an integrative literature review, of an exploratory nature, with a qualitative approach, carried out from April to June 2020. For the accomplishment of this study, the following databases were consulted: Medical Literature Analysis and Retrieval System Online (MEDLINE), Latin American and Caribbean Literature in Health Sciences (LILACS) and Scientific Electronic Library Online (SCIELO). The Health Sciences Descriptors (DeCS) were used in an associated way: Barré guillain syndrome; COVID-19; Neurology; Virus Infections. Then 704 studies with the proposed theme were initially considered; among these, 622 studies were excluded, according to the established exclusion criteria. After applying the inclusion criteria, 9 studies remained. The included studies were tabulated and critical and corroborative reviews were made between each of them. It is concluded that there is an increase in Guillain-Barré cases during viral outbreaks, with an increase in the incidence and the number of cases/month. In general, it is observed that among the main causes of Guillain-Barré Syndrome are infectious processes.